Research article Evaluation of Genotype MTBDRplus Assay for identifying Multidrug Resistant Mycobacterium tuberculosis isolates in Nepal - Dahal, B; Adhikari, N; Shah, Y; Simkhada, RC; Maharjan, B; Shrestha, B (Janaki Medical College Journal of Medical Science, 2013)
Background and Objectives: Multidrug-resistant (MDR) Mycobacterium tuberculosis strains are serious threats to the control of tuberculosis and comprise an increasing public health problem. Rapid detection of such strains is quite critical in timely management of such issues. The study was performed with an objective to compare Genotype MTBDRplus reverse hybridization probe assay (Hain Lifescince, GmBH, Nehern, Germany) with culture based proportion method for rapidly identifying MDR-TB strains from suspected multi drug resistant cases, referred to GENETUP Kathmandu, Nepal. Methodology: A commercially available new Genotype MTBDRplus assay was evaluated for its ability to detect mutations in Mycobacterial isolates conferring resistance to rifampicin (RMP) and isoniazid (INH). A total of 64 MDR isolates (i.e., at least resistant to RMP and INH), 5 fully susceptible strains and 1 RMP sensitive strains by conventional proportion method were analyzed using Genotype MTBDRplus assay. MTBDRplus assay is designed to detect the mutations in the hot spot region of rpoB gene, katG and regulatory region of inhA gene. Results: The MTBDRplus assay detected 59 of 61 RMP resistant strains (96.72%) with mutations on 81-bp hot spot region of rpoB gene and 60 of 63 INH resistant strains (95.23%) with mutation in codon 315 katG and regulatory region of inhA. The sensitivity and specificity for the detection of RMP resistance were 96.72% and 100% respectively. While, value of the same two variables for INH resistance were 95.23% and 100%, respectively. Conclusions: The new Genotype MTBDRplus assay represents a rapid, reliable, upgraded tool with high sensitivity and specificity for the detection of INH and RMP resistance strains that can readily be included in a routine laboratory work for the early diagnosis and control of MDR-TB. DOI: http://dx.doi.org/10.3126/jmcjms.v1i1.7884 Janaki Medical College Journal of Medical Sciences (2013) Vol. 1 (1):30-37